Lick It: Challenge the Way You Experience Food, Marijie Vogelzang (2022) - Ran Mei (International Journal of Food Design)
Review of: Lick It: Challenge the Way You Experience Food, Marijie Vogelzang (2022) Amsterdam: BIS Publishers, 224 pp., ISBN 978-9-06369-650-4, p/bk, €19.99